2001
DOI: 10.1310/kdm0-ru5w-nvtw-n9mc
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Nonadherence with Antiretroviral Drugs Predicts Persistent Condition

Abstract: Previous self-reported nonadherence was a strong predictor of persistent nonadherence during follow-up. Moreover, being of younger age and self-reporting vomiting or pruritus were also associated with a higher risk of nonadherence persisting over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 17 publications
0
10
2
Order By: Relevance
“…Alternatively, since the majority of Ugandan youth are unemployed, 17 their less stable economic situation might result in their being unable to meet travel and other costs associated with IPT. [18][19][20][21] Having no education or attaining only primary education was associated with a higher risk of LTFU. An earlier study by Wandwalo and Mørkve demonstrated significant differences in knowledge on TB disease and treatment according to the number of years of school education in Mwanza, Tanzania and its association with poor adherence and LTFU.…”
Section: Discussionmentioning
confidence: 98%
“…Alternatively, since the majority of Ugandan youth are unemployed, 17 their less stable economic situation might result in their being unable to meet travel and other costs associated with IPT. [18][19][20][21] Having no education or attaining only primary education was associated with a higher risk of LTFU. An earlier study by Wandwalo and Mørkve demonstrated significant differences in knowledge on TB disease and treatment according to the number of years of school education in Mwanza, Tanzania and its association with poor adherence and LTFU.…”
Section: Discussionmentioning
confidence: 98%
“…Similar findings of poorer adherence in younger age groups, especially those aged < 35 years, have also been reported in other studies. (32,33) Gender was not found to be associated with adherence in our study, similar to that reported by Fogarty et al (34) The level of education of PLWHA was also not found to be significantly associated with nonadherence in the present study, as was also reported by Cauldbeck et al (35) and Paasche-Orlow et al (36) Contrary to the findings of the study conducted in Pune and Delhi, (31) the PLWHA in the present study who were employed were more nonadherent to HAART than those who were unemployed. Probable causes of nonadherence among employed PLWHA are busy duty schedules in the workplace and/or forgetfulness.…”
Section: Discussionmentioning
confidence: 99%
“…The earlier studies generally aimed to identify predictors of nonadherence and often were embedded within clinical trials; later studies often involved sub-analyses of intervention trials. Six studies set out specifically to evaluate adherence measures (i.e., Martin-Fernandez, Escobar-Rodriguez, Campo-Angora, & Rubio-Garcia, 2001;Martin et al, 2001;Murri et al, 2001;Vincke & Bolton, 2002;Wagner et al, 2001;Walsh, Mandalia, & Gazzard, 2002).…”
Section: Findings From the Review Study Descriptionmentioning
confidence: 99%